2000
DOI: 10.1038/75144
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Two new NMR structures of WW domains, the mouse formin binding protein and a putative 84.5 kDa protein from Saccharomyces cerevisiae, show that this domain, only 35 amino acids in length, defines the smallest monomeric triple-stranded antiparallel beta-sheet protein domain that is stable in the absence of disulfide bonds, tightly bound ions or ligands. The structural roles of conserved residues have been studied using site-directed mutagenesis of both wild type domains. Crucial interactions responsible for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
161
1
9

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(181 citation statements)
references
References 24 publications
10
161
1
9
Order By: Relevance
“…6). Because several mutagenesis studies (10,(43)(44)(45) have established the importance of the Trp 6 -Pro 32 interaction for the folding and the stability of WW domains, we think that a similar strong intermolecular Trp-Pro interaction is used to promote protein-protein interactions between the WW domain and its substrates (46). The molecular mechanisms of the Pin1 function very recently became clearer through an elegant study by Zhou et al (17), who showed that Pin1 enhances in vitro the dephosphorylation of Cdc25C by the major transPro-directed phosphatase PP2A.…”
Section: Discussionmentioning
confidence: 99%
“…6). Because several mutagenesis studies (10,(43)(44)(45) have established the importance of the Trp 6 -Pro 32 interaction for the folding and the stability of WW domains, we think that a similar strong intermolecular Trp-Pro interaction is used to promote protein-protein interactions between the WW domain and its substrates (46). The molecular mechanisms of the Pin1 function very recently became clearer through an elegant study by Zhou et al (17), who showed that Pin1 enhances in vitro the dephosphorylation of Cdc25C by the major transPro-directed phosphatase PP2A.…”
Section: Discussionmentioning
confidence: 99%
“…The near UV spectrum in particular is a fingerprint of the tertiary structure, and even small structural perturbations can remarkably affect both its intensity and shape. The far-ultraviolet (UV) CD spectrum of both WT and mutant WW are typical of WW domains, having a positive band at 230 nm (44,49). This band is, however, not equally intense in the spectrum of the mutant, suggesting a lower content of secondary structure in the former (Fig.…”
Section: Spr Analysis Suggests a Loss Of Function For The Y65c Mutantmentioning
confidence: 99%
“…This is because the reversible nature of cellular signaling cascades favors weak interactions between the various underlying components (43,44).…”
Section: Binding Profiles Of the Mutated And Wt Ww Domains Onmentioning
confidence: 99%
“…The structures of the individual FBP21 WW domains are very similar to those of previously solved WW domain structures, and the pairwise r.m.s.d. of the ␤-sheet backbone atoms to the solution structures of WW domains from scPrp40 (7), hsFBP11 (22), mmFBP28 (39) are between 1.0 and 1.6 Å.…”
Section: Ww Domains Mediate the Interaction Of Fbp21 Withmentioning
confidence: 99%